An assessment of the genetic diversity and origin of the invasive weed Chromolaena Odorata (L.) King and Robinson in South Africa - Von Senger, Inge (Rhodes University, Faculty of Science, Botany Department, 2002)
Chromolaena odorata (L.) King and Robinson is an alien invasive weed to most of the Old World tropical regions of the earth, including South Africa where it is morphologically distinct from most other C. odorata plants examined from both its native and invasive range. It is thought that these morphological differences are related to difficulties encountered in successful establishment of biological control agents on the South African population of C. odorata. It has been postulated that the source population of the South African population will harbour potential biocontrol agents that will be suited to successful establishment on the South African plants. Several morphological, cytological and isozyme studies have been attempted to identify the source population of the South African population, but these have failed to identify the origin of the South African population. In this dissertation two PCR-based methods were attempted, in an investigation into whether the morphological differences and difficulties in establishment of biocontrol agents have a genetic basis. The two techniques attempted were: Inter Simple Sequence Repeat (ISSR) amplification, and DNA sequencing. Results could not be obtained using the ISSR method, and the reason for this was not discovered despite extensive trials. The internal transcribed spacer region and the external transcribed spacer region sequences were obtained from five samples, and compared. It was found that the ETS region gave more phylogenetic signal at the intraspecific level than the ITS region. However, due to difficulties in amplification of the external transcribed spacer region, work here focussed on obtaining Internal Transcribed Spacer sequences for 61 samples. Each of the samples sequenced had a unique ITS sequence, displaying a high level of intraspecific genetic diversity. The degree of this diversity is discussed with reference to the possible influences of polyploidy and concerted evolution on genetic structure. The ITS data indicated that some of the physical traits used to define 'morphotypes' of C. odorata were not correlated to genotype. From discussion and comparison of morphological character distributions and the ITS-based phylogeography it is suggested that the geographical origin of the South African population is Greater Antilelan, rather than from the continents of North and South America, which is where the Australasian, West African and Mauritian infestations are suggested to have originated.
Keywords: Biodiversity -- South Africa; Chromolaena odorata -- Biological control -- South Africa